Occupancy status of Malayan leopard prey species in a fragmented forest in Selangor, Malaysia. - Sanei, Arezoo; Hussin, Mohamed Zakaria (2011)
A study concerning prey availability for Malayan leopard (Panthera pardus delacouri Pocock 1930) in a highly fragmented secondary forest, namely: Ayer Hitam Forest Reserve located in Selangor, Malaysia was conducted from February 2008 to March 2009. The main objectives of this study were to investigate (i) a priori unknown leopard potential prey species existed in the study area and (ii) occupancy status of a priori known leopard potential preys with regard to the presence of anthropogenic factors in the habitat. Findings suggested that leopards in Ayer Hitam Forest Reserve feed mainly on Eurasian wild pig (Susscrofa) supplemented by macaque and lesser mouse deer (Tragulus javanicus). Occupancy and detection probabilities for wild boar, macaque and mouse deer were relatively high indicating that there is no evidence of lack of prey sufficiency in the study area. Moreover, there is a high probability of encountering prey species for each leopard individual throughout the forest. We identified four active anthropogenic disturbance factors in the study area (i.e. plantation, construction, deforestation and presence of indigenous and local settlements). Construction activities had the most profound effect on occupancy status of wild boar and macaque while mouse deer was mostly affected by deforestation activities. This study indicated that although there is little concern regarding prey sufficiency, lack of space and presence of active anthropogenic disturbances are the most critical factors in determining leopard population viability in the study area.